Removal of Pollutants in Different Landfill Leachate Treatment Processes on the Basis of Organic Matter Fractionation. Issue 2 (1st March 2018) - Zolfaghari, Mehdi; Dia, Oumar; Klai, Nouha; Drogui, Patrick; Brar, Satinder Kaur; Buelna, Gerardo; Dubé, Rino
Abstract : A combination of processes was required for the proper treatment of old landfill leachate, as it contained a high concentration of pollutants. Humic substances comprised half of the total organic carbon in the raw leachate. Mobility of di(2‐ethylhexyl) phthalate (DEHP) and metals could depend on the fate of these substances. Characterization of carbon in raw leachate and effluent of the membrane bioreactor, biofiltration, electro‐oxidation, electro‐coagulation, and nanofiltration showed complete removal of suspended solids and colloids. Physical processes could not remove the hydrophilic fraction due to its lower molecular weight. However, high removal of the hydrophilic fraction with a molecular weight <500 Da was expected in the biological process. In comparison with fulvic acid, larger sized humic acid resulted in complete removal by physicochemical processes. Because of DEHP partitioning on dissolved organic matter, especially on humic substances, its removal could be correlated with total organic carbon removal. Metals such as iron, aluminum, magnesium, and lead showed removal efficiency >80% in biological processes. Electro‐deposition on the surface of an electrode and precipitation by hydroxide resulted in removal efficiencies >90 and >50% in electro‐coagulation and electro‐oxidation, respectively. Rejection of metals by nanofiltration was >80% and depended on the size and charge of cation. All in all, a combination of membrane bioreactor and nanofiltration seems to be the optimal process configuration for efficient treatment of old landfill leachate. Core Ideas: Humic substances comprise half of the organic carbon in landfill leachate. Given its size & interaction with sludge, fulvic acid is the most concerning type of carbon. Organic carbon with size 0.5 to 10 kDa is rarely removed by biological treatment. We study the fate of metal & hydrophobic emerging contaminants bound with humic substances. Combination of biological treatment & nanofiltration is the most efficient treatment option.